USE OF UPADACITINIB IN 11 TOFACITINIB-REFRACTORY ULCERATIVE COLITIS PATIENTS AT A SINGLE TERTIARY CARE CENTER. (26th January 2023) - Levine, Jake; McKibbin, Jey; Ham, Rebecca; Higgins, Peter; Bishu, Shrinivas; Berinstein, Jeffrey
Abstract: INTRODUCTION: Ulcerative colitis (UC) is a chronic inflammatory condition characterized by diarrhea, abdominal pain, rectal bleeding, and weight loss. Upadacitinib is an oral, selective, small molecule Janus Kinase (JAK) inhibitor that was recently approved in the United States for moderate to severe UC. Clinical trials evaluating the efficacy of upadacitinib excluded patients with a previous exposure to tofacitinib, a nonselective JAK inhibitor; therefore, the efficacy of upadacitinib in patients with previous exposure to tofacitinib remains largely unknown. METHODS: We present a small retrospective case series of all patients with a diagnosis of ulcerative colitis seen at our institution between with a prior exposure to tofacitinib who were initiated on upadacitinib between May and August of 2022. Demographic data was collected as well as outcome data on clinical improvement, steroid-free remission, biochemical improvement, colectomy status, and adverse events. RESULTS: Eleven tofacitinib-refractory patients with ulcerative colitis were initiated on upadacitinib. Mean age was 38.1 years, five (45.5%) patients were female, nine (81.8%) patients were white, seven (63.6%) patients had pancolitis, and mean duration of UC was 7.4 years (Table 1 ). In this group, there were high rates of prior targeted therapy failures. These patients were followed for a mean of 121 days. The clinical course of each patient is presented in Table 2 . Of the 11 patients included in our study, nine (81.8%) patients reported symptomatic improvement, six (54.5%) patients were able to successfully taper corticosteroids, and two (18.2%) patients underwent colectomy, one of which was elective and planned prior to initiating upadacitinib. The mean fecal calprotectin improvement was 1430mg/kg of patients with both baseline and follow-up testing. Three (27.3%) patients experienced an adverse event; two (18.2%) patients with mild COVID-19 not requiring hospitalization and one (9.1%) patient with Enteropathogenic E. Coli. DISCUSSION: This real-world single-center case series of 11 patients, suggests that upadacitinib may be an effective option for patients with a previous tofacitinib exposure. Larger prospective studies are needed to confirm these findings.